Keanekaragaman Makrofauna Tanah Dalam Proses Dekomposisi Awal Seresah Dari Hutan Sekunder dan Tegakan Kemiri Di Lereng Pegunungan Gawalise Sulawesi Tengah - Melati, Rima Hasiani; Wardah, Wardah; Yusran, Yusran (Mitra Sains, 2021)
This study aims to determine litter production, decomposition rate and diversity of soil macrofauna in secondary forests and candlenut stands. This research was carried out by collecting litter on the littertrap for 30 days then put it on the litterbag, then observed in secondary forests and candlenut stands in Uwemanje Village, Kinovaro District, Sigi Regency, Gawalise Mountains Slope, Central Sulawesi. Macrofauna identification was carried out at the Pest Laboratory, Faculty of Agriculture, Tadulako University, Palu, from October to December 2019. Parameters observed were litter production, decomposition rate and soil macrofauna. The results showed that secondary forest litter production (2.20 tons / ha / month) was higher than candlenut stands (2.14 tons / ha / month). The rate of litter decomposition in secondary forests is classified as moderate with a percentage of 17% -19% and the decomposition rate of candlenut stands is relatively slow with a percentage of 10-12%. The diversity of soil macrofauna species in secondary forests is similar to candlenut stands. Similarity index or similarity of soil macrofauna types in secondary forests and candlenut stands is worth 75.67%.